Adaptation and Innovation Strategies for Islamic Education Curriculum in the Digital Era 4.0 - Firdaus Munif Qasthalani; Hafidz; Malik Ibrahim ‘Aliyuddin; Ahmad Dimas Fahrezy; Afifah Azahra Prihasti; Fatimah Azzahra Ayu Sandera; Aqgit Qizty Muriska; Syafarani Sucifirdiasti (Bulletin of Islamic Research, 2025)
This article discusses how Islamic education adapts and innovates in curriculum development in the digital era 4.0. While digital technology provides many opportunities, there are various challenges that must be faced, such as limited access to technology, lack of digital skills among teachers, differences between Islamic values and modern technology, and cultural barriers. Through a literature review, this article emphasizes the importance of building a curriculum that combines technology with Islamic values, improving teachers' digital skills, and utilizing technology wisely. This research aims to keep Islamic education relevant and competitive in the digital era without losing the Islamic identity that is the foundation.